Relationship between BMI, PSA and Histopathological Tumor Grade in a Caucasian Population Affected by Prostate Cancer - Tirabassi G; Gioia A; Manco R; Tenaglia R.L; Balercia G (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
The aim of this work is to show the relationship between obesity and aggressivenes of Prostate Cancer. We conducted a retrospective study of 132 men affected by Prostate Cancer underwent radical prostatectomy. Gleason score was abstracted by biopsy specimens and by post-operatory specimens. We evaluated PSA level and Body Mass Index (BMI). The prevalence of Post Operative Gleason Score > 8 among subjects with lowest tertile of PSA was higher in obese (BMI > 30 Kg/m2) (94.4%) vs overweight subjects (BMI 25-29.9 Kg/m2) (19.2%) (p< 0.01); the prevalence of Post Operative Gleason Score >8 among subjects with second tertile of PSA was higher in obese (100%) and overweight (70%) vs normal weight subjects (0%) (p<0.01 and p<0.001 respectively); the prevalence of Post Operative Gleason Score >8 among subjects with third tertile of PSA was higher in obese (100%) and overweight (62%) vs normal weight subjects (0%) (p<0.05 respectively).We believe that changes in the levels of PSA and Gleason Score, observed as a function of class BMI, could be due to separate mechanisms: PSA levels could be influenced by the effect of dilution by increased plasma volume of the subjects obese, while tumor grade could be affected by the hormonal changes induced by adipose tissue.